Measuring risk attitudes among Mozambican farmers - de Brauw, Alan; Eozenou, Patrick (Elsevier, 2014)
Although farmers in developing countries are generally thought to be risk averse, little is known about the actual form of their risk preferences. In this paper, we use a relatively large lab-in-the-field experiment to explore risk preferences related to sweet potato production among a sample of farmers in northern Mozambique. A unique feature of this experiment is that it includes a large subsample of husband and wife pairs. After exploring correlations between husband and wife preferences, we explicitly test whether preferences follow the constant relative risk aversion (CRRA) utility function, and whether farmers follow expected utility theory or rank dependent utility theory in generating their preferences. We reject the null hypothesis that farmers' preferences follow the CRRA utility function, in favor of the more flexible power risk aversion preferences. If we make the common CRRA assumption in our sample, we poorly predict risk preferences among those who are less risk averse.